2017
DOI: 10.18348/opzool.2017.2.77
|View full text |Cite
|
Sign up to set email alerts
|

The first combined checklist of earthworms of the Northeastern Mediterranean region (Clitellata: Megadrili).

Abstract: Abstract. The first combined checklist of earthworms of the Balkan Peninsula, Anatolia, the Levant and Cyprus is presented. Out of the 226 taxa, 216 belong to the Holarctic family Lumbricidae. Ten further species are from the families Criodrilidae, Acanthodrilidae, Ocnerodrilidae and Megascolecidae. The widely introduced peregrine species take part with 11.9% (27 taxa). The number of endemics within the studied areas is highest on the Balkan Peninsula (90 taxa). As a result of this study, four synonyms were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Mršić, 1991) [41]. Several members of this group have been recorded as present in the Balkan peninsula [41,42]. Our finding locality is very close to the Croatian locality given for O. croaticus by Mršić (1991), whereas O. bretscheri (like O. juvyi in France) seems to be confined to mountain habitats.…”
Section: Species Delimitation For Oligochaetes and Collembolanssupporting
confidence: 71%
See 1 more Smart Citation
“…Mršić, 1991) [41]. Several members of this group have been recorded as present in the Balkan peninsula [41,42]. Our finding locality is very close to the Croatian locality given for O. croaticus by Mršić (1991), whereas O. bretscheri (like O. juvyi in France) seems to be confined to mountain habitats.…”
Section: Species Delimitation For Oligochaetes and Collembolanssupporting
confidence: 71%
“…Due to prior knowledge about the insufficiency of BOLD and NCBI GenBank data on Oligochaetes from Croatia and the need for further metabarcoding of this group, an especially careful morphological examination of the Oligochaete specimens was carried out, which revealed that they belong to the genus Octodrilus Omodeo, 1956. This genus has a main distribution center in the Balkan Peninsula and the identification of the species has been attempted using regional checklists and identification keys (e.g., Mršić, 1991;Szederjesi, 2017) [41,42]. Only sexually mature specimens were considered, because species diagnoses are mainly based on the position of the clitellar structures and the arrangement of internal reproductive structures.…”
Section: Morphological Analysismentioning
confidence: 99%
“…Octodrilus transpadanus is a widely distributed Trans-Aegean species It lives from Switzerland, to Turkey in Europe and also North and South America. So, in our present knowledge, Turkey is easternmost country where the species was found up until now (Csuzdi and Zicsi, 2003;Szederjesi, 2017). Knowledge about the diversity of earthworms is insufficient because of the majority of the country yet to be studied .…”
Section: Discussionmentioning
confidence: 92%
“…Dendrobaena (Omodeo & Rota 1989, Omodeo & Rota 1991; Aegean (Omodeo & Rota 1991; Inner Anatolia ; Mediterranean (Csuzdi et al 2007; South-East Anatolia (Pavlíček et al 2009. Zoogeographical distribution type: A widely distributed trans-aegean species recorded from Switzerland to Turkey (Csuzdi and Zicsi, 2003;Szederjesi 2017).…”
Section: Resultsmentioning
confidence: 99%
“…For long-term storage, 200 specimens were preserved in 96 % ethanol and stored at −40 °C. Using a stereo microscope, the individuals were identified based on available morphological keys [ 58 , 59 ].…”
Section: Methodsmentioning
confidence: 99%